A lunar rhythm in the nocturnal foraging activities of wintering Barnacle Geese - Ydenberg, R C; Prins, H H Th; van Dijk, J. (Wildfowl, 1984)
Observations were made on the night-time foraging of Barnacle Geese Branta leucopsis wintering on Schiermonnikoog in the Dutch Waddenzee. Night foraging took place only around full moon. As the moon waxed, the geese fed both by day and by night, but at the full moon, they fed only at night. Foraging abruptly reverted to its normal rhythm after the full moon. The visibility of the moon seemed to play no role in the night-time activity of Barnacle Geese, nor did day-time disturbances seem important. The similarity of these observations to those of inland roosting Lapwings Vanellus vanellus and Curlews Numenius arquata in England, which also invert their foraging routine around full moon, leads us to suggest that, like these birds, Barnacle Geese may have been hunting for invertebrates whose activity was keyed to a lunar cycle.